A Themed Issue of Functional Molecule-based Magnets: Dedicated to Professor Masahiro Yamashita on the Occasion of his 65th Birthday - Katoh, Keiichi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Research on molecule-based magnetic materials was systematized in the 1980s and expanded rapidly. A Special Issue focusing on molecule-based magnetic substances was published in Magnetochemistry. However, the functionalities of the substances increase daily; therefore, the researchers’ quest is not yet in decline. Research on molecule-based magnetism developed across many fields, including chemistry, physics, material chemistry, and applied physics, and the use of the various functionalities of these molecule-based magnetic substances has greatly influenced research on spin-based devices. In honor of Professor Masahiro Yamashita, who contributed greatly to this field, I have put together a Special Issue that highlights ten groundbreaking articles. The issue is entitled, “A Themed Issue of Functional Molecule-Based Magnets: Dedicated to Professor Masahiro Yamashita on the Occasion of his 65th Birthday”. I wish to thank the authors for their dedicated work, and the referees and editorial staff for the time they invested commenting on the articles.